2017
DOI: 10.1002/anie.201708971
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Radical Anions Triggered by Bacteria In Situ for Selective Photothermal Therapy

Abstract: A supramolecular complex that can be selectively reduced to radical anions in situ by facultative anaerobic bacteria is reported. To this end, a water-soluble bifunctional monomer bearing perylene diimide was synthesized, and its supramolecular complex with cucurbit[7]uril was fabricated on the basis of host-guest complexation, which could be reduced to forming radical anions in the presence of E. coli. It was found that this supramolecular complex could display different ability of generating radical anions b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
151
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(151 citation statements)
references
References 54 publications
0
151
0
Order By: Relevance
“…The related mechanism is depicted in Figure A. The locally increased temperature (more than 50 °C) generated by the solar light‐activated photothermal reaction can provide lethality through hyperthermia and irreversible bacterial destruction, eventually killing bacteria . Additionally, the direct thermalization in fibrous RP can consume the photon energy, and the rest of the band edge energy located in the infrared region may also result in the generation of heat and be thermally absorbed by the vibration of the crystal lattice .…”
Section: Resultsmentioning
confidence: 99%
“…The related mechanism is depicted in Figure A. The locally increased temperature (more than 50 °C) generated by the solar light‐activated photothermal reaction can provide lethality through hyperthermia and irreversible bacterial destruction, eventually killing bacteria . Additionally, the direct thermalization in fibrous RP can consume the photon energy, and the rest of the band edge energy located in the infrared region may also result in the generation of heat and be thermally absorbed by the vibration of the crystal lattice .…”
Section: Resultsmentioning
confidence: 99%
“…Another type of a PTT system that has selective bacterial recognition properties is the CB[7] protected supramolecular complex CPPDI ( Figure ), which is triggered by a chemical reductive response. Xu and Zhang et al reported that PDI group in the complex are selectively reduced by facultative bacteria like E. coli to form radical anions, while aerobic bacteria like B. subtilis do not . As mentioned above, PDI radical anions exhibit the capacity of photothermal conversion under NIR irradiation.…”
Section: Antibacterial Supramolecular Systems Based On Photothermal Amentioning
confidence: 95%
“…These key interactions can arise from unique surface properties of pathogenic bacteria, including pH, shapes and chemical reductive responses. By utilizing supramolecular strategies and accurate recognition systems, more effective photothermal systems have been designed for PTT of bacteria.…”
Section: Antibacterial Supramolecular Systems Based On Photothermal Amentioning
confidence: 99%
See 1 more Smart Citation
“…Recently,Zhang et al reported that hydrogenases,which are present in abundance on membranes of facultative anaerobic bacteria, promote reduction of as upramolecular complex (CPPDI) to form radical anions,w hich then induce antibacterial effects. [23] Inspired by this interesting report, we reasoned that if hydrogenases facilitate the type Ip hotoreaction promoted by irradiation of NanoPcA, then ahigher level of photoinactivation would be occur against facultative anaerobic bacteria compared to aerobic bacteria (Figure S11a). To assess this proposal, ap reliminary study was conducted to compare the relative PDT growth inhibitory effects of NanoPcA against P. aeruginosa (aerobic,G ramnegative) and E. coli (facultative anaerobic, Gram-negative).…”
Section: Angewandte Chemiementioning
confidence: 96%